0
$\begingroup$

I am having problems finding the inverse Fourier transform of:

$$\frac{1}{(1+iw)(2+iw)}$$

I think I could use convolution property but I'm stuck. I know that:

$$ f(t) = e^{-at} H(t) \implies f(w) = \frac{1}{(a+iw)}$$

Can somebody help me?

$\endgroup$
  • 5
    $\begingroup$ Use partial fraction expansion $\endgroup$ – Mark Viola Jul 5 '18 at 23:15
  • $\begingroup$ Thanks so much! $\endgroup$ – emee Jul 5 '18 at 23:32
  • $\begingroup$ You're welcome. My pleasure $\endgroup$ – Mark Viola Jul 6 '18 at 2:45
1
$\begingroup$

We write

$$\frac{1}{(1+j\omega)(2+j\omega)}$$

As

$$\frac{A}{(1+j\omega)}+\frac{B}{(2+j\omega)}$$

Then we have

$$A+B=0$$ $$2A+B=1$$

$$A=1$$ $$B=-1$$

Then

$$\mathcal{F}^{-1}(\frac{1}{(1+j\omega)(2+j\omega)})$$

$$=(e^{-t}-e^{-2t})u(t)$$

Where $u(t)$ is the Heaviside function

Note: there may be a constant of $\sqrt{2\pi}$ depending on conventions being used

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.